Radiotherapy driven immunomodulation of the tumor microenvironment and its impact on clinical outcomes: a promising new treatment paradigm - Umair Mahmood (Taylor & Francis Group, 2021)
Traditional treatment approaches for advanced malignancies have been associated with limited clinical outcomes necessitating the development of novel therapies. However, the ability of radiotherapy to induce pro-immunogenic changes in tumor immune microenvironment can be leveraged when combined with systemic agents. Radio-immunotherapeutic initiatives employing the use of monoclonal antibodies, genetically engineered T cells, cytokines and virus-vector mediated gene therapies have demonstrated promising potential for the management of various solid malignancies. Future studies incorporating biomarker enrichment strategies and radiobiological variables could pave the way for immune-oncology based personalized medicine approaches to be integrated in standard of care practices for the treatment of challenging clinical populations.